FAKTOR FAKTOR YANG MEMENGARUHI MANAJEMEN PAJAK - Cyntia Verensia; Meiriska Febrianti (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study to analyzed the factors that affect tax management on manufacturing companies in Indonesia. This study selected eight variabels are profitability, leverage, firm size, fixed asset intensity, tax facility, inventory intensity, independent commissioner, and institutional ownership as independent variables. Sampel of this research used in manufacturing companies which is listed on Indonesia Stock Exchange (IDX) over the 3 (three) years period 2018-2020. There were 77 companies met the criteria, resulting 231 data are taken as samples. The selection of samples used purposive sampling method. Data were analyzed using multiple linear regression. The result of research showed that profitability have effect on tax management. Where as, leverage, firm size, fixed asset intensity, tax facility, inventory intensity, independent commissioner, and institutional ownership have no effect on tax management.